Entrepreneur as an Individual Review of Recent Literature on Entrepreneurial Skills - Normalini Md Kassim2, Muhammad Salman Shabbir1, (Opción, 2019)
The purpose of this paper is to provide some rich and deepinsight to explore the characteristics, traits and key features ofindividual Entrepreneur via comparative qualitative research methods.As a result, entrepreneurial skills required to undertake innovativeendeavors are formed through the value that shaped by the social,economic and cultural aspects of being a self-employment person. Inconclusion, it is probable that one can classify the set of skills can beclassified as entrepreneurship skills that are distinct in nature fromother leader and management skills.